KEBIJAKAN PEMERINTAH INDONESIA MENINGKATKAN EKSPOR PRODUK HOLTIKULTURA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Teguh Hidayat; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the policy Indonesia Government increased of horticulture product toward Asean Economic Community in 2015. Asean Economic Community are one of part Asean Community in economic scope. In Asean Economic Community were be held a common market and skill labour and product in South East Asia Region. In ordre that Indonesia have to create a some policy to increase their natural and human resources.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy Indonesia Government increased of horticulture product toward Asean Economic Community. The theories applied in this research are merchantilism perspective with international cooperation theory.The conclusion of the research about the policy Indonesia Government increased of horticulture product toward Asean Economic Community are doing a increase competitiveness of horticulture product and coordination between institution likes Indonesia Government implemented efficiency product, optimalization of land in BUMN, cooperation between provate sector to investation in production sector and implemented a Supply Chain Management and use a institutional farmer approach to increase a horticulture product.Key words: policy, horticulture, Asean Economic Community.